2020
DOI: 10.3390/jcm9082418
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cells in Diffuse Large B Cell Lymphoma

Abstract: Diffuse large B cell lymphoma (DLBCL), known as the most common non-Hodgkin lymphoma (NHL) subtype, is characterized by high clinical and biological heterogeneity. The tumor microenvironment (TME), in which the tumor cells reside, is crucial in the regulation of tumor initiation, progression, and metastasis, but it also has profound effects on therapeutic efficacy. The role of immune cells during DLBCL development is complex and involves reciprocal interactions between tumor cells, adaptive and innate immune c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 113 publications
(122 reference statements)
0
33
0
Order By: Relevance
“…Thus, a better understanding of the interactions between the TME and the immune response may provide new approaches to improve the efficiency of current immunotherapies, especially immune checkpoint inhibitor and chimeric antigen receptor (CAR) T cell therapies ( 8 ). Several studies have considered the latent role of the TME in the occurrence and development of DLBCL, but their results were controversial ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a better understanding of the interactions between the TME and the immune response may provide new approaches to improve the efficiency of current immunotherapies, especially immune checkpoint inhibitor and chimeric antigen receptor (CAR) T cell therapies ( 8 ). Several studies have considered the latent role of the TME in the occurrence and development of DLBCL, but their results were controversial ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…TNFAIP3 is poorly expressed in DLBCL. DLBCL is the most common histological subtype of NHL (17)(18)(19) and generally responds well to treatment with rituximab (20,21). TNFAIP3 is an established tumor suppressor in lymphoma (22)(23)(24), but its drug resistance has been reported in various types of cancer (25,26).…”
Section: Resultsmentioning
confidence: 99%
“…GSVA, GO, and KEGG enrichment results showed that cluster B, which had an abundance almost the same as that of immune cells, was strongly associated with cytokine activity and the chemokine pathway. This phenomenon may be related to the fact that immune cells are capable of producing multiple types of cytokines and chemokines (Tamma et al, 2020).…”
Section: Discussionmentioning
confidence: 99%